Fatores condicionantes na retomada das atividades cr??ticas da empresa: um estudo de caso em projetos de continuidade de neg??cios - Melchiori, Sergio Luis Mattos (2017)
This study aimed to understand the conditioning factors that influence the effective recovery of the organization's critical activities. This research was done through a case study with exploratory type and qualitative and descriptive approach, with twenty business continuity professionals in a multinational insurance company. It was identified in the literature eight factors that influence the recovery of critical activities and their respective importance within the context of a business continuity project, and the factor simulated exercises was consider the least important and the business continuity plan the most important factor in the recovery of the company's activities. It was observed that the employees of the company???s case study, despite the support of senior management, had a low confidence in the resumption of critical activities, which is basically due to the factors: simulated exercises, which are not realistic enough; awareness programs, which does not include all those involved with business continuity; and the business continuity plan, which does not clearly show the resources and strategies that the company has in a holistic way.